A retrospective study to assess clinical characteristics and time to initiation of open-triple therapy among patients with chronic obstructive pulmonary disease, newly established on long-acting mono- or combination therapy - Mapel, Douglas (Int J Chron Obstruct Pulmon Dis, 2017)
INTRODUCTION: An incremental approach using open-triple therapy may improve outcomes in patients with chronic obstructive pulmonary disease (COPD). However, there is little sufficient, real-world evidence available identifying time to open-triple initiation. METHODS: This retrospective study of patients with COPD, newly initiated on long-acting muscarinic antagonist (LAMA) monotherapy or inhaled corticosteroid/long-acting β(2)-agonist (ICS/LABA) combination therapy, assessed baseline demographics, clinical characteristics, and exacerbations during 12 months prior to first LAMA or ICS/LABA use. Time to initiation of open-triple therapy was assessed for 12 months post-index date. Post hoc analyses were performed to assess the subsets of patients with pulmonary-function test (PFT) information and patients with and without comorbid asthma. RESULTS: Demographics and clinical characteristics were similar between cohorts in the pre-specified and post hoc analyses. In total, 283 (19.3%) and 160 (10.9%) patients had moderate and severe exacerbations at baseline, respectively, in the LAMA cohort, compared with 482 (21.3%) and 289 (12.8%) patients in the ICS/LABA cohort. Significantly more patients initiated open-triple therapy in the LAMA cohort compared with the ICS/LABA cohort (226 [15.4%] versus 174 [7.7%]; P<0.001); results were similar in the post hoc analyses. Mean (standard deviation) time to open-triple therapy was 79.8 (89.0) days in the LAMA cohort and 122.9 (105.4) days in the ICS/LABA cohort (P<0.001). This trend was also observed in the post hoc analyses, though the difference between cohorts was nonsignificant in the subset of patients with PFT information. DISCUSSION: In this population, patients with COPD are more likely to initiate open-triple therapy following LAMA therapy, compared with ICS/LABA therapy. Further research is required to identify factors associated with the need for treatment augmentation among patients with COPD.